Study on the Design of an Embedded on-line Cleaning Condenser Tube Robot - Yuan Fucai; Liang Kaihui; Wang Nianzheng; Yang Lei (Jixie chuandong)
In order to improve a cleaning robot working performance on the condenser tube inner wall and solve problems of the existing cleaning equipment like low efficiency and high cost,a new type cleaning robot is developed to be used in the condenser tube. Based on the working condition and the actual requirements of the cleaning work,a cleaning robot mechanical body structure,an anti-interference pipe rotary connector,a cleaning operation mode and workflow are designed. Furthermore,the design of the robot transmission system is analyzed,the flow chart of the design and calculation is presented,then the automatic analysis,calculation and the transmission system self-checking can be realized. This research not only provides a new type of embedded on-line cleaning robot for the condenser tube inner wall,but also presents a theoretical basis for the design of similar robots in future.